Inside the Southeast Asian kitchen - Tan, Su-Lyn.; Oshima, Neal M.; Tan, Christopher, 1972-. ([S.l.] ArtPostAsia Pte Ltd., 2007)
Inside the Southeast Asian Kitchen takes you a step further by showing you how you can create the heady flavors of this region's cuisines in your own kitchen. It features over 80 authentic recipes for home-cooked dishes from ten Southeast Asian nations (Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand and Viet Nam) and draws together, in one volume, the work of some of Southeast Asia's most respected food writers and culinary experts. Each chapter begins with an introduction to the culinary history, foodlore and tradition of one Southeast Asian nation, and shares age old culinary wisdom that was once more likely to be imparted at a grandparent's dinner table or by the communal kitchen fire. Inside the Southeast Asian Kitchen captures the very essence of what makes this region so unique and shares, through clearly-explained recipes, some of its most delicious and beloved home-cooked dishes.
Foreword -- Introduction -- The Southeast Asian kitchen -- Brunei Darussalam -- Cambodia -- Indonesia -- Lao PDR -- Malaysia -- Myanmar -- Philippines -- Singapore -- Thailand -- Viet Nam -- About the country contributors -- Glossary -- Weights and measures -- Index -- Acknowledgments.
At head of title: Foodlore & flavors.
Keywords: Cooking, Southeast Asian; Cookimg, Asia Southeastern; Cooking, Philippine